Community Empowerment Through Increasing IKABEL Stick Production in Ohoitel Village, Tual City: Pemberdayaan Masyarakat Melalui Peningkatan Produksi Stik IKABEL di Desa Ohoitel Kota Tual - Anna Maria Ngabalin; Hasyim, Cawalinya Livsanthi; Kristhina Priskila Rahael; Elisabeth Cory Ohoiwutun; Tati Atia Ngangun; Usman Madubun; Roberto Mario Kabi Teniwut; Esmeralda Ongirwalu; Emiliana Ohoirat (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program focuses on the empowerment of the Rahanyam UMKM group producing Stik IKABEL (fish, moringa, and enbal), a healthy snack with high nutritional value. The selection of this topic stems from the potential of local ingredients and the necessity to improve production efficiency. The methods implemented included training on machine use, production techniques, and marketing strategies. The anticipated outcome is an increase in production capacity, a better understanding of financial management, and enhanced promotional strategies. These improvements will significantly contribute to the sustainability of the Rahanyam UMKM group and help elevate the local economy.